Pemberdayaan Komunikasi pada Masyarakat Desa Wisata Kinahrejo Cangkringan, Kabupaten Sleman, Yogyakarta - Andra Pahresi Kurniawan; Puji Hariyanti (Program Studi Ilmu Komunikasi UII, 2022)
This study aims to identify and analyze the communication process of community empowerment based on the opportunities and obstacles experienced by the people of Kinahrejo, Cangkringan, the Tourism Village, in Sleman Regency Yogyakarta. The results showed that community empowerment activities in Kinahrejo Tourism Village consisted of an awareness process, a capacity-building process, and a communication method empowerment process. The communication pattern built is interactive with the person-by-person treatment and simultaneous communication